A Comprehensive Systematic Review of The Relationship between Types of Combination Therapy (Oral and Topical) on the Healing Duration of Tinea Imbricata - Agustina Vonny Moa (International Medical Journal Corp. Ltd, 2025)
Introduction: Tinea imbricata is a chronic, recalcitrant dermatophyte infection caused by Trichophyton concentricum, predominantly affecting populations in tropical and subtropical regions. The infection is characterized by concentric, scaly plaques that are often difficult to treat, leading to high relapse rates. Despite various available antifungals, optimal treatment strategies, particularly the role of combination therapy (oral and topical), remain inadequately defined, especially concerning healing duration (A. Leung et al., 2019; Al-Bassam Rana Abdulazeem et al., 2019). Methods: A comprehensive systematic review was conducted to evaluate the relationship between types of combination therapy (oral and topical) and the healing duration of tinea imbricata. Literature screening was performed across multiple databases using predefined criteria focusing on human studies with clinically/mycologically confirmed tinea imbricata, combination therapy interventions, and quantifiable healing outcomes. Data extraction covered treatment regimens, healing duration, patient characteristics, study design, long-term outcomes, and safety profiles from included studies. Results: Out of 33 identified sources, only three specifically addressed tinea imbricata, with the majority examining other dermatophytoses. Combination therapies, such as oral terbinafine or itraconazole paired with topical agents (e.g., amorolfine, sertaconazole, keratolytic ointments), demonstrated faster initial response and significantly lower relapse rates compared to monotherapy. For instance, at 2 weeks, itraconazole combined with topical iodine achieved 75.9% improvement versus 24.1% for itraconazole alone (Thamir Abdulmajeed Kubaisi, 2022). Complete cure typically required 4-8 weeks, with extended duration improving outcomes. Safety profiles were generally comparable to monotherapy, with gastrointestinal symptoms being the most common adverse events. Discussion: The synthesized evidence indicates that combination therapy is particularly advantageous for chronic, recalcitrant, or treatment-resistant infections, likely due to synergistic antifungal mechanisms and enhanced drug penetration. The heterogeneity in study findings can be attributed to variations in infection severity, patient populations, and study designs. The strongest evidence supporting combination therapy comes from comparative studies with adequate follow-up, showing substantial reductions in relapse rates (e.g., 7% vs. 57% for itraconazole + terbinafine vs. itraconazole alone) (Yagub S. Saleh et al., 2025). Conclusion: Combination antifungal therapy, integrating oral and topical agents, appears to reduce healing duration and relapse rates in difficult-to-treat dermatophytosis, including tinea imbricata. For uncomplicated cases, monotherapy may suffice with adequate duration. Future high-quality, randomized controlled trials focusing specifically on tinea imbricata are essential to establish standardized, evidence-based treatment protocols.